Integrating Religious Moderation into Education: A Qualitative Analysis of the ASSTA Curriculum in Madrasahs - Mohamad Maulidin Alif Utama; Dirga Ayu Lestari; Dedek Nurisiti Khodijah; Sangkot Sirait; Karwadi Karwadi; Sa'adi Sa'adi; Mukh Nursikin; Mansur Mansur (AL-ISHLAH: Jurnal Pendidikan, 2025)
The internalization of religious moderation is essential in fostering tolerance and harmony in Indonesia’s pluralistic society. This study explores how the ASSTA curriculum—comprising the Qur'an, Sunnah, Science, Technology, and Morals—is integrated into the learning process to instill religious moderation in students at Madrasah Ibtidaiyah (Islamic elementary schools). This qualitative research employed a phenomenological approach to understand the lived experiences of teachers and students. Data were collected through classroom observations, in-depth interviews, and questionnaires distributed to 20 purposively selected respondents from MI Asy-Syukriyyah in Tangerang. The data were analyzed iteratively using reduction, coding, and thematic analysis. Findings indicate that religious moderation is not explicitly taught as a standalone subject, but is embedded as a “hidden curriculum” throughout various learning activities. Teachers integrate moderation values contextually through discussions, collaborative projects, and real-life applications, aligning with the principles of contextual teaching and learning (CTL). The curriculum’s integration resulted in improved student engagement, enhanced understanding of moral values, and increased tolerance in classroom interactions. Quantitative indicators—collected through pre- and post-implementation surveys—show a significant improvement in students’ moral awareness and social behavior. The study concludes that the ASSTA-based curriculum offers a strategic framework for embedding religious moderation in early education. However, sustainable implementation requires continuous teacher training, community involvement, and curriculum evaluation. This research contributes to the discourse on Islamic education reform and provides a practical model for integrating moderate religious values within a competency-based curriculum.